Hudud Terhadap Pencurian dan Penodongan atau Perampokan Dibandingkan Dengan Ketentuan Hukum Pidana Positif Indonesia - Duwi Handoko (Prodi Siyasah (Hukum Tata Negara) Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2019)
Allah exaggerated the threat of punishment for the perpetrators of the hijab above the threat of punishment for the perpetrators of murder or theft. This threat applies not only if the acts of hirabah are committed to Muslims, but also if they are carried out to other religious people who live under Islamic rule. Allah has mentioned the forms of punishment for the perpetrators of hirabah crimes, namely being killed (if they are only human lives without robbery), killed by crucifixion (if killing and seizing the victim's property), crossing their arms and legs crossed (those who only seizing property and not killing the victim), disposed of (if only the perpetrator commits terror or scares the victim by threatening). The threat of punishment for violent theft according to Article 365 of the Criminal Code is: Article 365 paragraph (1) of the Criminal Code (imprisonment for a maximum of nine years), Article 365 paragraph (2) of the Criminal Code (imprisonment for a maximum of twelve years), Article 365 paragraph (3) of the Criminal Code (jail sentence of fifteen years at the most). Article 365 paragraph (4) of the Criminal Code (capital punishment or life imprisonment or for a certain period of twenty years at the most).